Trends in research on the perioperative use of acupuncture in the last 20 years: A CiteSpace-based bibliometric analysis and literature review - Zhang, Minjuan; Cairen, Zhuoma; Zhang, Junbao; Wang, Yun; Lu, Zhihong (Frontiers in Anesthesiology, 2022)
Objective Research on acupuncture-related techniques in the perioperative period has been increasing in the last 20 years. In this research, a bibliometric analysis was performed to review the application of acupuncture for perioperative medicine and to evaluate the trends in research on the perioperative use of acupuncture. Methods CiteSpace was used to analyze published papers on the perioperative use of acupuncture in the Web of Science database from 2001 to 2021. The research trends were evaluated based on the number of publications, keywords, journals, countries, institutions, and authors. Moreover, collaborative networks and reference co-citation network maps were analyzed. Results A total of 719 related studies were included in the analyses. The number of annual publications has gradually been increasing. Evidence-Based Complementary and Alternative Medicine published the most (49 articles). Regarding the cited journals, Anesthesia & Analgesia ranked first in terms of frequency (361), while Pain ranked first in terms of centrality (0.71). China (284) and the China Medical University (26) published the most. Wang Yu (21 articles) was the most active author, while Lee A (116) was the most co-cited author. The most co-cited reference was a meta-analysis of acupuncture for post-operative pain (212). The “post-operative cognitive dysfunction” cluster was new research directions that had recently emerged. Pain-related keywords had the highest frequency in keywords about indications. Conclusion Research on perioperative acupuncture is a promising field, and more cooperation in global scientific research is needed. Our results may help researchers in identifying potential collaborators, research frontiers, and hot topics.